Handshake, No. 5 (April 2012) - International Finance Corporation (International Finance Corporation, Washington, DC, 2015)
This issue includes the following headings: seeds and soil: smallholder agriculture; innovation: pairing commercial buyers with rural producers; grain storage: a ready role for public-private partnerships (PPPs); agricultural clusters: powering Africas agricultural potential; and interviews: AgDevCo, bill and Melinda gates foundation, earth policy institute.